Universities as Learning Organizations in a Cross-cultural Perspective - Jerome Dumetz (Управленческое консультирование, 2018)
Objective: The paper attempts to link the concepts of Learning Organizations and Organizations culture with Universities within a cross-cutural perspective. Methods: After a review of literature of Learning Organizations, the author provides insight of Organizational culture definitions and attempts to analyses the challenges of cross-cultural studies for those organizations. Results: The review showed that learning organizations have been successful in implanting change. Because each University has a unique profile an ad-hoc cross-cultural analysis is needed. Conclusions/Recommendations: The debate whether Universities are learning organizations is still open. Yet, in order to become accomplished learning organizations, they should take into account their cross-cultural challenges